Penerapan Model Pembelajaran SPICS (Student Centered, Problem Based, Interest, Confident and Satisfaction) Untuk Meningkatkan Hasil Belajar IPA Terpadu Siswa Kelas VII MTs Negeri Pamenang Tahun Ajaran 2018/2019 - Arifin, Hadi Nur; Putra, Apriza Hongko; Yulianti, Eni (STKIP YPM Bangko, 2018)
This research was motivated by the learning outcomes of students in MTS NegeriPamenang Integrated Science learning, most of them are still under the classicalKKM set by the school, this shows that the Integrated Science learning process hasnot run optimally. This study aimed to improve Integrated Science learningoutcomes for grade VII MTS N Pamenang students with the application of SPICS(Student Centered, Problem Based, Interest and Confident and Satisfaction)learning models, in class VII MTS N Pamenang in the 2018/2019 school year. Thietype of research was classroom action research, where the subjects in this studywere students of class VII MTS N Pamenang consisted of to 28 people, while theobject in this study was SPICS Learning Model (Student Centered, Problem Based ,Interest, Confident and Satisfaction). The procedure in this study consisted of thestages of planning, implementing actions, observation and evaluation andreflection. Data collection form of student and teacher activity observation sheetsand evaluation test used. Students have received grades according to the KKM,meaning that action research in the second cycle has achieved a minimum target of75% achievement of students achieving KKM. Based on the research resultsobtained in the first cycle the average test score of 73.03 cycle with a percentageof completeness 64% or 19 students who graduated according to the defined KKMthat is 75 in the second cycle found that student learning outcomes increased to77.57. Based on the data analysis, the research can be concluded that by usingSPICS (Student Centered, Problem Based, Interest, Confident and Satisfaction)learning models, it can improve the learning outcomes of class VII MTS NPamenang in the 2018/2019 school year.